Characteristic Analysis of Annual Sediment Transport Modulus of Xijiang River Basin in Guangxi over Last 60 Years - ZHU Yingjie (Renmin Zhujiang)
Mann-Kendall rank correlation test,Spearman rank correlation test and Mann-Whitney-Pettitt abrupt change point analysis were performed to study the trend and mutation components of the annual sediment transport modulus of the Xijiang River Basin.Then,the kriging interpolation method was used for spatial interpolation in the mean and trend of the annual sediment transport modulus.After a double cumulative curve was drawn,the hydrological analysis method was employed to examine the causes of the changes in the annual sediment transport modulus.The results show that the average annual sediment transport modulus of the Xijiang River Basin increased in the 1960s—1970s but kept decreasing in the 1980s.The multi-year sediment transport modulus drops gradually from west and east to northeast in the 1960s,from outer to central in the 1970s,from northwest and east to south and northeast in the 1980s,from northwest and east to central and northeast in the 1990s,and from east and west to north in 2000—2009.In general,the multi-year average sediment transport modulus of the upper reaches is greater than that of the middle and lower reaches.Without the influence of precipitation change,the variation of the annual sediment transport modulus of the Xijiang River mainly results from human activities affecting the erosion and sediment yield of the basin.The contribution rate of precipitation change to the sediment transport modulus is 6.3%~12.3%,whereas that of human activities is 87.7%~93.7%.